Sensory acceptance testing and rheological parameter analysis of a plant-based cocoa (Theobroma cacao l.) dessert formulated with chickpeas (Cicer arietinum L.), quinoa (Chenopodium quinoa Willd.), sweet potatoes (Ipomoea batatas L.), and rice (Oryza sativa L.) - Camila Araújo Costa Lira; José Diogo da Rocha Viana; Larissa Morais Ribeiro da Silva; Socorro Vanesca Frota Gaban (Food Chemistry Advances)
The growing demand for sustainable and nutritious food alternatives has driven innovation in plant-based product development. Rich in fiber, protein, and bioactive compounds, plant-based ingredients offer functional and health-promoting properties while reducing environmental impact. In this context, the formulation of dairy-free desserts represents a promising strategy to meet consumer preferences for both health and sustainability. This study aimed to develop a creamy plant-based cocoa dessert using chickpeas, quinoa, sweet potatoes, and rice. The effects of sugar and cocoa levels on consumer acceptability were evaluated using Response Surface Methodology (RSM). Eleven dessert formulations were developed based on a Face-Centered Central Composite Design. Microbiological analyses confirmed product safety, with Escherichia coli below 3.0 MPN/g, coagulase-positive Staphylococci under 10 CFU/g, and absence of Salmonella. High determination coefficients (R² > 0.90) were observed for aroma, color, overall impression, and purchase intention, color reached R² > 0.99. Consumer acceptance scores were also high: flavor (92.44 %), aroma (89.77 %), texture (89.47 %), color (94.22 %), and overall appearance (93.66 %). The optimal formulation was determined to contain 3 % cocoa and 10 % sugar. These results offer a solid foundation for the large-scale development of plant-based desserts, supporting innovation in sustainable and consumer-accepted food products.